Functionalization of thermoswitchable liposomes for rapid detection of Gram-negative bacteria - Tan, Jie Ren (2022)
Biosensors for rapid and sensitive detection of pathogens play a crucial role in healthcare and food safety. Despite the development of numerous sensing devices, it remains a challenge to obtain biosensors that are reliable, easy-to-use and can offer results within minutes. Herein, we report a functionalized liposome, with an embedded fluorescent dye to offer thermoswitchable emission, for selective Gram-negative bacteria detection. This targeting system utilizes polymyxin B (PmB) as a recognition element, where it can be conjugated onto the surface of the liposome to differentiate Gram-negative bacteria from Gram-positive counterparts as well as mammalian cells via fluorescence spectroscopy. The unique thermoswitchable fluorescence conferred through manipulation of aggregation-induced quenching allows for high signal-to-noise detection, reaching up to 3.5-fold increase in emission in the case of E. coli. This is in contrast to typical small organic fluorescent labels and future work includes developing a suitable capture probe to achieve lower limits of detection.